Attitudes towards feminism predict susceptibility to feminism‐related fake news. Issue 5 (9th June 2021) - Murphy, Gillian; Murray, Emma; Gough, Doireann
Summary: False memories may be especially likely when one is exposed to misinformation that is consistent with one's beliefs. Here, we assessed whether feminist attitudes predict susceptibility to feminism‐related fake news. In Experiment 1 ( n =  1537), the more negative participants' attitudes towards feminism, the more likely they were to report a false memory for a fabricated event that negatively reflected on the feminist movement, and vice‐versa. This effect was only evident for those who interpreted the event as expected (e.g., those who rated the event as bad for feminism). When the purpose of the study was revealed, feminist attitudes also predicted ability to identify the stories as fake. We replicated these findings in Experiment 2 ( n =  786), using fake stories that were less ambiguous. This study suggests that individuals are more susceptible to false memories for fake news stories that are ideologically congruent, even after a warning.